Analisis pajak restoran dan pajak hotel terhadap pertumbuhan pendapatan asli daerah Kota Manado - Kalalo, Liony E.; Runtu, Treesje; Kindangen, Wulan D. (Yayasan Widyantara Nawasena Raharja, 2024)
Taxes are the main source of state revenue. Regional taxes are divided into two parts, provincial taxes and district/city taxes. According to Law no. 1 of 2022 restaurant tax and hotel tax are included in district/city taxes. Restaurant tax and hotel tax are important contributors to the PAD revenue of the city of Manado. The aim of this research is to see the contribution of restaurant taxes and hotel taxes to Original Local Government Revenue (PAD) in Manado City from 2021 to 2023 with contribution percentages in accordance with applicable regulations. This type of research uses qualitative descriptive methods. Based on the results of research conducted at the Manado City Regional Revenue Agency, the percentage of restaurant tax contribution to PAD was 97.26% and the percentage of hotel tax contribution to PAD was 68.3%. The realization of restaurant taxes and hotel taxes increases every year. This shows that restaurant tax makes the largest contribution to Manado City's Original Regional Income.